STRES KERJA DAN KEPUASAN KERJA GURU-GURU DI RINTISAN SEKOLAH BERTARAF INTERNASIONAL (RSBI) - Kusumadewi, Sherlly; Wijono, Sutarto; Prapunoto, Susana (Noetic Psychology, 2011)
The aim of this study is to measure the relationship between job stres and job satisfaction using TARSQ (Teacher Attribution of Responsibility for Stres Questionnaire) ÃÂ adapted from McCormick and TJSQ (Teacher Job Satisfaction Questionnaire) adapted from Lester. The participants were the teachers from private Junior High School Surakarta (SMP 3K Surakarta). There were 41 teachers involved in this study. The determinants of Job Stres that have been examined under this study include personal aspect, behavior aspect, cognitive aspect, physiology aspect, and organizational aspect. The aspect of Job satisfaction are challenging work, promotion and salary, working condition, colleagues, and leadership. Pearson Correlation analyses were used to investigate the hypothesized relationship. The result showed r = -0.392 with p = 0,011 < 0.05. There was a negative significant relationship between job stres and job satisfaction.ÃÂ Keywords: job stres, job satisfaction, TARSQ, TJSQ